Hybrid Agency in Co-Configuration Work - Virkkunen, Jaakko (Outlines. Critical Practice Studies, 2006)
This article maintains that a new wave in the development of the productive forces of society triggered by the revolution in information and communication technologies is taking place. Production carried out by single organizations is increasingly replaced by forms of production that are based on close long-term collaboration between specialized firms. This transition reflects the increasing importance of research and development as well as collective learning in business competition. New information and communication technologies enable new forms of distributed and collaborative knowledge creation and learning. The article explores an emerging new form of innovation-oriented inter-firm collaboration called co-configuration and the new kind of dualistic agency it seems to be calling for. In this form of collaboration the traditional boundary between producer and provider as well as the boundaries between product development, sales and maintenance within the provider organization become blurred. The article presents a case of the development of co-configuration work in the provision of optimization software for pulp production. The case shows some of the contradictions involved in this new form of collaboration and the development of a new kind of object-oriented collaborative agency mediated through a real-time information and communication technological platform and uniting two processes of continuous development.